Characterization of kenaf/jute epoxy hybrid composites for aircraft food tray - Khan, Tabrej (2020)
This research investigation is aimed to find mechanical, physical, thermal, non-destructive properties and morphological of kenaf/jute hybrid composites. This investigation has been spared into four stages with the archived specific objectives. The first stage focuses on the mechanical behavior of kenaf jute hybrid composites such as untreated and treated kenaf/jute hybrid composites properties. The woven kenaf and jute have been treated with distilled water with 6% (NaOH) for two hours at room temperature. Kenaf and jute are in mat form, and Epoxy resin has been used to fabricate the hybrid composites by using the hand layup method as well as kenaf/jute fibers are loaded with 30% by weight. The mechanical investigation, tensile, flexural, impact, and a compression test have shown impressive results. The second stage investigates the physical properties such as water absorption, thickness swelling, and density behaviors of hybrid composites and after the investigation, the overall results are depicted in these sections. The outcome seems that the thermal stabilities of the untreated kenaf and jute fibers are slightly higher than the treated fabrics. This investigation results show when compared to the treated with the untreated, the performances of treated hybrid composites are slightly different and the kenaf /jute hybrid composites with 30% treatment provide excellent physical and mechanical properties but in this case of thermal properties, it is not much effected. Low-velocity impact test has been conducted on the hybrid composites of kenaf and jute hybrid composites. The results show that only a K/J/K layer laminate has withstood impact energy below 30 Joules, and it has failed when the impact energy is approached with 35 Joules. Hence, the novel hybrid composites can be used for product development in environmentally friendly technologies. The fourth stage presents aircraft food tray table which is made using the kenaf/jute hybrid, and belongs to an internal part of the Boeing B737-800 aircraft food tray table. Here, it has also been tested with some parameters compared to real applications such as weight free-fall drop test.